2021
DOI: 10.9745/ghsp-d-20-00502
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Antimicrobial Supply Chain in Bangladesh: A Scoping-Review-Based Ecological Assessment Approach

Abstract: A standardized method for evaluating antimicrobial supply chains in the context of access and use could be a useful tool in assessing national capacity to implement programs that address antimicrobial resistance. We present both a novel ecological approach comprising mapping and the use of indicators that can be used to characterize national antimicrobial supply chains as well as benchmark countries and, for the first time, a country-level assessment of Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…There is a scarcity of data on the pattern of antibiotic dispensing in pharmacies in Bangladesh according to the WHO AWaRe classification; however, a recent report showed that a high proportion (86%) of Watch group antibiotics were used for the suspected cases of COVID–19 with SARI [ 33 ]. A recently published article on mapping the antimicrobial supply chain in Bangladesh showed that most (54%) of the top ten antibiotics in terms of sales belonged to the Watch group, followed by 39% in the Access group, which is comparable to our study findings [ 31 ]. However, the WHO recommends that Access group should comprise at least 60% of the national antibiotic consumption to support AMR mitigation [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is a scarcity of data on the pattern of antibiotic dispensing in pharmacies in Bangladesh according to the WHO AWaRe classification; however, a recent report showed that a high proportion (86%) of Watch group antibiotics were used for the suspected cases of COVID–19 with SARI [ 33 ]. A recently published article on mapping the antimicrobial supply chain in Bangladesh showed that most (54%) of the top ten antibiotics in terms of sales belonged to the Watch group, followed by 39% in the Access group, which is comparable to our study findings [ 31 ]. However, the WHO recommends that Access group should comprise at least 60% of the national antibiotic consumption to support AMR mitigation [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…A recent study jointly conducted by the Directorate General of Drug Administration (DGDA), Bangladesh, and the WHO reported in 2021 that the sale of antibiotics increased by 31%, and most antibiotics were sold without a registered physician’s prescription [ 30 ]. A report on mapping the antimicrobial supply chain in Bangladesh showed that in terms of sales, most (54%) of the top ten antibiotics belonged to the Watch and 39% in the Access groups [ 31 ]. A recent study in Bangladesh on suspected cases of COVID-19 with severe acute respiratory infections (SARI) reported multiple antibiotics were prescribed to a number of individuals with a higher proportion of Watch group (86%), followed by the Access and Reserve groups [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of effective regulations, there is a risk for large number of antibiotics including medically important antibiotics becoming available for purchase by fish farmers over the counter without a prescription. Our study identified a diverse class of antibiotics used in aquaculture, including tetracyclines, fluoroquinolones, macrolides, and aminoglycosides, which was in accordance with previous reports in Bangladesh [ 25 , 27 , 29 , 35 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…We believe that pharmacists who are experts in medicine inventory management and forecasting may benefit resource-deprived developing countries ( 56 , 58 ); therefore, consulting and utilizing pharmacist expertise may ease the burdens of procurement. In other developing countries, pharmacists are involved in medicine supply chain management ( 59 ). Consequently, we consider adopting a similar approach for the Fijian livestock sector.…”
Section: Discussionmentioning
confidence: 99%